TAX BEHAVIOR: AVOIDANCE VS EVASION (ANALYSIS OF INDICATORS OF THE EUROPEAN UNION AND THE WORLD) - Merkulova, Tamara (Social Economics, 2024)
The article is devoted to the study of behavioural aspects of taxation. A significant problem of effective taxation is taxpayers’ reduction of tax liabilities through shortcomings in tax laws, uncertainty in their statements, direct violation of tax norms, and the use of illegal schemes to reduce the tax base. Taxpayer behaviour is of key importance for the effectiveness of tax policy, filling the budget, and performing state functions, which determines the relevance of this issue.The object of the analysis presented in the article is tax behaviour types: tax avoidance and tax evasion. The research purpose is to identify the relationship between GDP, as a general indicator of socio-economic development, and tax revenue loss due to tax abuse. Taking into account the important role of offshores in legal and illegal schemes for reducing tax liabilities, an indicator of offshore wealth was involved in the analysis. The preliminary research hypotheses are based on the methodology of behavioral economics. The identification of the relationship between indicators was carried out using correlation analysis.A comparative analysis of the character and strength of the relationship between variables carried out for the sample of 174 countries of the world and the set of the European Union (27 countries) uncovered significant differences between these sets. The most important finding is that the strength of the relationship between GDP and each tax behaviour type in the European Union is the same and stronger than in the general set, where tax avoidance dominates tax evasion.Analysis of the European Union countries sample showed that offshore wealth has a very close relationship with losses caused by both tax behaviour types, in contrast to the general set of countries, where tax avoidance has a weaker relationship (correlation 0.64 versus 0.91). This confirms the more active involving offshore technologies in tax behaviour in European countries compared to the general sample.